Utfodringstider och foderberikningar : påverkan på Linderödssvins (Sus scrofa domestica) beteende och välfärd i djurparksförhållande - Svensson, Louise (SLU/Dept. of Animal Environment and Health (until 231231), 2018)
Pigs are omnivores and in the wild they spend most of their time foraging. When pigs are held for production or in zoos they often get fed in a feeding trough. That means that they cannot express any foraging behaviour which may lead to the development of stereotypies and a bad welfare. The captive environment is usually predictable with few changes in the environment and in the feeding schedule. Some studies suggest that a predictable environment can lead to stereotypies and inactivity which can be signs of a bad welfare. On the other hand, some studies suggest that a predictable environment can lead to anticipating behaviours which may be a sign of good welfare. The purpose of this study was to observe changes in pigs’ behaviour and activity when presented with a feeding machine that spread out food in the enclosure. The feeding machine started at either predictable or unpredictable times. It was then discussed if some of these treatments could increase the pigs’ natural behaviour, activity and welfare. The pigs observed in this study were two Linderödssvin at Skansen, a zoo in Sweden. The observations took place before and after they were fed in the morning, before and after the feeding machine started and one time at the day when they were not fed. The pigs’ activity decreased compared to the baseline when they were not fed. This result may be because they were fed with more food during the study period than before. Studies has shown that animals that were fed with more food were more inactive during the day than animals fed with a smaller amount of food. The result in this study showed an increase in natural behaviours and activity when the feeding machine spread out food compared to when they received food in a trough, and may therefor indicate enhanced welfare. The pigs were more active before the feeding machine started at predictable times but more active after the machine started at unpredictable times. It was however unclear if any of the particular schedules increased the animal welfare.